Toasty / Nurizzah Roslan … [et al.] - Roslan, Nurizzah; -, Nurul Fatini; -, Salmi Nadhirah; -, Nur Elliya Deana; Husain, Nor Azmawati; Ibrahim, Khalilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
A toaster is a simple kitchen appliance that can be used to lightly cook and toast bread slices to make them crispier, darker, and tastier. Every kind of toast may be the same for everyone. Using a cutting-edge and innovative toaster can provide greater benefits to users. Toasty is made with Advanced Toast Technology, which ensures consistent results each time. In this invention, three features have been added to the toaster to make it more convenient for the user. Toasty comes with a transparent cover, as well as a 4-slot toaster and a removable crumb tray. Toasty, for example, provides users with a transparent cover that prevents dust from collecting on the toaster, a 4-slot toaster that can help users to save time as it simplifies their daily affairs and includes a removable crumb tray for easy cleaning. The main goal of this invention is to be the first toaster that people buy when they required toaster that offer more clean features.